Demonstration of TNSA proton radiography on the National Ignition Facility Advanced Radiographic Capability (NIF-ARC) laser. (12th November 2021) - Simpson, R A; Mariscal, D A; Kim, J; Scott, G G; Williams, G J; Grace, E; McGuffey, C; Wilks, S; Kemp, A; Lemos, N; Djordjevic, B Z; Folsom, E; et al.
Abstract: Proton radiography using short-pulse laser drivers is an important tool in high-energy density (HED) science for dynamically diagnosing key characteristics in plasma interactions. Here we detail the first demonstration of target-normal sheath acceleration (TNSA)-based proton radiography the NIF-ARC laser system aided by the use of compound parabolic concentrators (CPCs). The multi-kJ energies available at the NIF-ARC laser allows for a high-brightness proton source for radiography and thus enabling a wide range of applications in HED science. In this demonstration, proton radiography of a physics package was performed and this work details the spectral properties of the TNSA proton probe as well as description of the resulting radiography quality.